No Life Without You : Refugee Love Letters from the 1930s - Felsenstein, Frank 1944- HerausgeberIn (Open Book Publishers, 2024)
The letters and journals of Ernst Moritz and Vera Hirsch Felsenstein, two German Jewish refugees caught in the tumultuous years leading to the Second World War, form the core of this book. Abridged in English from the original German, the correspondence and diaries have been expertly compiled and annotated by their only son who preserves his parents’ love story in their own words. Their letters, written from Germany, England, Russia, and Palestine capture their desperate efforts to save themselves and their family, friends and businesses from the fascist tyranny. The book begins by contextualizing the early lives of Moritz and Vera. Because the letters are written to each other almost daily, they are incredibly immediate. Most centrally, the letters recount an astonishing love story, sensual in its intimate detail, and full of dramatic pathos in revealing the anxieties of being apart as the Nazi threat unfolds and broadens. It is told through the voices of two exceptionally articulate letter writers. This volume offers insights into the moral and psychological dilemmas faced by German Jews as a targeted community. It affords a unique appreciation of the impact of historical and socio-political upheavals on the lives of a persecuted minority. A scholarly introduction by Rachel Pistol draws out the main themes raised by this correspondence, observing its relevance to contemporary debates about migration and political authority